Strategi Guru Pendidikan Agama Islam dalam Mewujudkan Pembelajaran Interaktif, Inspiratif, Menyenagkan, Menantang, dan Memotivasi, (I2m3). di Smp Negeri 2 Samaturu - Ansar Ansar; Zakariah Zakariah; Nursyalim Nursyalim (Syntax Idea)
This research discusses the Strategies of Islamic Religious Education Teachers in Realizing Interactive, Inspiring, Fun, Challenging, and Motivating Learning, (I2M3). This study aims to determine (1) Islamic Religious Education Teachers' Strategies in Creating Interactive, Inspiring, Fun, Challenging, and Motivating, (I2M3). (2) the supporting and inhibiting factors faced by Islamic Religious Education Teachers in realizing Interactive, Inspirational, Fun, Challenging, and Motivating Learning, (I2M3). at SMP Negeri 2 Samaturu. This type of research is Qualitative Research. Data was collected by means of interviews, observation and documentation. The data is processed by descriptive analysis. The results of the study (1) The strategy used by Islamic Religious Education Teachers in realizing I2M3 Learning is that most students are active and enthusiastic in learning by using several learning methods. (2) the supporting factors of this learning process are supported by the teacher's ability to use unique methods in each delivery of learning and are also supported by the readiness of students in participating in learning. As for the inhibiting factors of the learning process, namely the facilities and infrastructure at Samaturu 2 Public Middle School are inadequate or still limited, the learning environment at Samaturu 2 Public Middle School is less strategic because the location of the school is close to the provincial road so that the noise of vehicles can disturb the concentration of students in learning, as well as limited time allocation even though the use of learning methods requires a lot of time. The Islamic Religious Education Teacher's strategy that is used should not only be applied to PAI subjects but can be used for all subjects by adapting the strategies used to the existing situations and conditions.